2017
DOI: 10.1007/s00280-017-3388-4
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin co-administration does not increase irinotecan (CPT-11) toxicity in colorectal cancer patients

Abstract: This study did not identify an increase in CPT-11 toxicity by co-administration with CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently, Makihara et al . conducted a study to evaluate the influence of concomitant use of clarithromycin, a potent CYP3A4 inhibitor, on irinotecan toxicity. The study did not identify an increase in irinotecan‐induced toxicity by coadministration of clarithromycin .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Makihara et al . conducted a study to evaluate the influence of concomitant use of clarithromycin, a potent CYP3A4 inhibitor, on irinotecan toxicity. The study did not identify an increase in irinotecan‐induced toxicity by coadministration of clarithromycin .…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant reduction in the incidence of grades III-IV neutropenia in the experimental group but no differences in grades III-IV diarrhoea [17]. Recently, Makihara et al [18] conducted a study to evaluate the influence of concomitant use of clarithromycin, a potent CYP3A4 inhibitor, on irinotecan toxicity. The study did not identify an increase in irinotecan-induced toxicity by coadministration of clarithromycin [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is theoretically possible that patients with CYP3A4-metabolized drug treatments would experience increased drug toxicities when co-administration of CYP3A4 inhibitors. However, a (Makihara et al, 2017), possibly due to uridine diphosphate glucuronosyltransferase isoform 1A1, organic anion transporter 1B1, genetic variation factors such as irinotecan-induced wide interindividual variability in drug response and toxicity (Riera et al, 2018). More detailed studies on individualized dose adjustment for cancer patients in clinical practice may be accomplished by developing a combined population pharmacokinetic model of irinotecan and its metabolites to prevent adverse effects caused by excessive drug/metabolite accumulation (Oyaga-Iriarte et al, 2019).…”
Section: Concomitant Drugs Involving Inhibition or Induction Of Cyp3a...mentioning
confidence: 99%
“…Nevertheless, the usefulness of antibiotics for the duration of CPT11 chemotherapy is controversial. Retrospective analyses conducted at Osaka National Hospital (Osaka, Japan) revealed no difference in the prevalence of grade-3–4 diarrhea between the co-administration group (clarithromycin and CPT11) and the CPT11-monotherapy group in patients with colorectal cancer ( Makihara et al., 2017 ). Another retrospective study found that antibiotics did not improve the therapeutic efficacy of CPT11 in advanced colorectal cancer ( Imai et al., 2020 ).…”
Section: Microbiota As An Intermediary In the Efficacy And Toxicity Of Cpt11 Chemotherapymentioning
confidence: 99%